10(x-4)=6x-12

Simple and best practice solution for 10(x-4)=6x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(x-4)=6x-12 equation:


Simplifying
10(x + -4) = 6x + -12

Reorder the terms:
10(-4 + x) = 6x + -12
(-4 * 10 + x * 10) = 6x + -12
(-40 + 10x) = 6x + -12

Reorder the terms:
-40 + 10x = -12 + 6x

Solving
-40 + 10x = -12 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-40 + 10x + -6x = -12 + 6x + -6x

Combine like terms: 10x + -6x = 4x
-40 + 4x = -12 + 6x + -6x

Combine like terms: 6x + -6x = 0
-40 + 4x = -12 + 0
-40 + 4x = -12

Add '40' to each side of the equation.
-40 + 40 + 4x = -12 + 40

Combine like terms: -40 + 40 = 0
0 + 4x = -12 + 40
4x = -12 + 40

Combine like terms: -12 + 40 = 28
4x = 28

Divide each side by '4'.
x = 7

Simplifying
x = 7

See similar equations:

| 10=-2*5c | | 4c+5y-1+3x=11 | | 6(x-2)=-3x+32 | | 2n+15=180 | | 9x-8y=2 | | 6d+21=4d+7 | | 64=-4(6p+2) | | 3x+5-1+3+4x=14 | | (x+3)(x+1)=0 | | 17x=180 | | 10=-2c | | 6(5x+4)(3x-1)=0 | | v+42-3v=-34 | | 9g+8g=17 | | 8[5-3]=0 | | 3[2a-4]=0 | | 2c+a=-3c+44 | | 2z+5+3z=10 | | -5x^2+15x-9=0 | | -3[r+4]=21 | | -5w(w-3)(w+2)=0 | | -3[r+4]=-21 | | 5[q+6]=-20 | | 5[q+6]=20 | | 8x-9=33-4x | | 5x+7=2x-9 | | -3(-4-6x)=84 | | x^3+2x^2+4=0 | | -y+3z=9 | | 12+18x=84 | | 2+18x=84 | | 6x-6x=-2 |

Equations solver categories